Membaca Bentuk Dan Pola Geometri Dalam Motif Batik Kawung - Anastasia Desmeria Br Ginting; Dessy Kartika Sari; Khairunnisa Nasution; Immanuel Hasiholan Siregar; Imel Fitaloca Tambunan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
As one of Indonesia's cultural heritage recognized by UNESCO, the Kawung motif holds a wealth of deep aesthetic, philosophical, and symbolic values. Studies on the geometric forms and patterns in the Kawung motif not only offer a better understanding of cultural heritage, but also open up opportunities to explore the relationship between art, mathematics, and philosophy. This research aims to explore the geometric forms and patterns in the Kawung motif in depth, by integrating perspectives from art, mathematics, and philosophy. By analyzing the geometric structure and mathematical principles underlying this motif, as well as relating them to the symbolic and philosophical meanings contained within, it is expected to gain a more holistic understanding of Indonesia's cultural heritage and the intellectual wealth it possesses.